Wayang Topeng Pedalangan: Body movements of selected characters in Jatipitutu Pitutujati / Syafiq Faliq Alfan - Syafiq Faliq , Alfan (2015)
Wayang Topeng Pedalangan in Jogjakarta is a type of dance theatre with its actor wearing mask, not to be confused with Wayang Wong Mataraman which does not involve all of the actors wearing mask. The masks used can be divided into seven categories which are; (1)Mask of strong character (gagah), (2) Mask of halus character, (3) Mask of princess (putri), (4) Mask of monster character (raksasa), (5) Mask of monkeys (kera), (6) Mask of Panakawan and (7) Mask of animal characters. Another distinct features of Wayang Topeng Pedhalangan are the repertoire use which are the stories from Panji epic. The epic tells about a prince from the kingdom of Jenggala named Panji Asmarabangun or Panji Inu Kertapati, who is going to be betrothed with a princess from the kingdom of Kediri named Galuh Candrakirana or Dewi Sekartaji. During the night of the wedding, the princess had been kidnapped from the garden of keputèn by a siluman woman. Thus, the search begins and the prince also begins his journey far and wide to search his beloved one. Dewi Sekartaji too suddenly appears in a forest and begins her journey to find her beloved prince, Panji Asmarabangun. Through the guidance of the gods (Dewa), both of them need to change their appearance and need to search for each other in their journey so they can be united once again. It is interesting that Wayang Topeng Pedhalangan in Jogjakarta has not been covered widely and only recently when Dr. Sumaryono submitted his theses on ‘The Role of Dalang in the life and development of Wayang Topeng Pedhalangan Jogjakarta’ in 2011. This research however concerns with the mechanics of the acting during a performance, and such, the objective of this study are 1. To understand the important aspect of body movement of selected Wayang Topeng Pedalangan characters including the presentation of the traits of particular characters in ‘Jatipitutu Pitutujati’. 2. To understand the training process of Wayang Topeng Pedalangan actors in preparing for a performance. 3. To understand the process needed for a Dalang to acquire and to understand the correct body language for each selected characters. 4. To examine the problems connected with the use of masks in the process of developing characters and their presentation. Through interviews with actors and those who participates in the performance and by watching two recorded performances of Wayang Topeng Pedhalangan Jogjakarta “Jatipitutu Pitutujati”, each character in the performance will be analyze in terms of its acting mechanic using semantic theory and the basic concept of language of dance where the movement will be break down to small gestures and movement to see the mechanics of how a character move and how they carry a dialogue and communicate with other characters. The outcome of this study is to see what is the body language perceived by the Wayang Topeng Pedalangan Jogjakarta community towards each character in the performance.